“What is the first thing that comes to your mind when you see this picture?” A case study on multimodal indirectness in social media content of a sex toy manufacturer - Savolainen, Taru (My University, 2024)
The thesis examines the indirectness and directness strategies in multimodal discourse on sex toys on the social media platform Instagram. The research was conducted from a case study standpoint. A preliminary review of different sex toy brands showed that indirectness is utilised in order to discuss the topics of sex and sexuality. To collect a manageable dataset, the German sex toy manufacturer Fun Factory was selected as the main subject of the study. The company has a long history in the business and an established presence on social media. The theoretical background on indirectness is based on the literature by Allan and Burridge (1991; 2006) that discusses x-phemisms. X-phemism is an umbrella term for euphemisms, dysphemisms and orthophemisms. Euphemisms are indirect expressions, that camouflage the reference to a taboo topic in a socially acceptable way. Dysphemism on the other hand are indirect words and phrases that are considered rude or disrespectful, such as swearwords. Orthophemisms then encompass terms that are considered neutral and straightforward, like medical vocabulary. The material is further analysed through multimodal discourse analysis, specifically image-text relations described by Kress and van Leeuwen (2006) and Barthes ([1977] 1990). The linguistic theories are supplemented with the description of the historical context of sex toy selling buying. Rules and regulations of the platform are also revised, as they affect the environment that the company has to operate in. The dataset in itself consists of 131 Instagrams posts, including their text descriptions and a total of 346 images. Both qualitative and quantitative methods were used in the analysis. Phenomena that showed low numbers in the quantitative analysis revealed to be impactful in relaying the wanted message in the qualitative examination. Ultimately, both visual and verbal indirectness were utilized to create meaning. The indirectness was constructed with x-phemisms but also with other strategies. The results further revealed that indirectness and directness overlapped across the data. Thus, assigning the examples to clear categories deemed challenging. This shows that the discourse is a mixture of levels and strategies in order to transmit an understandable message with the limitations that the platform sets. Keywords: Indirectness, Directness, X-phemism, Euphemism, Dysphemism, Visual Euphemism, Multimodal analysis, Content analysis, Image-text relations, Social media, Sex toys
Keywords: Indirectness, Directness, X-phemism, Euphemism, Dysphemism, Visual Euphemism, Multimodal analysis, Content analysis, Image-text relations, Social media, Sex toys